Structurisation and visualisation of design space for launch vehicle with hybrid rocket engine. (2016) - Chiba, Kazuhisa; Kanazaki, Masahiro; Watanabe, Shin'ya; Kitagawa, Koki; Shimada, Toru
A single-stage launch vehicle with hybrid rocket engine has been conceptually designed by using design informatics, which has three points of view, i.e., problem definition, optimisation, and data mining. The primary objective of the present design is that the down range and the duration time in the lower thermosphere are sufficiently secured for the aurora scientific observation, whereas the initial gross weight is held down to the extent possible. The multidisciplinary design optimisation was performed by using a hybrid evolutionary computation. Data mining was also implemented by using a self-organising map and the stratum-type association analysis. Polypropylene and liquid oxygen with swirling flow are adopted as solid fuel and liquid oxidiser, respectively. The condition of single-time ignition is assumed in flight sequence. Consequently, the design information regarding the tradeoffs, the behaviours of the design variables in the design space to become the non-dominated solutions, and the implication of the design variables for the objective functions have been obtained in order to quantitatively differentiate the advantage of hybrid rocket engine. The structurisation of the design space has been implemented in order to observe the effectiveness of the local regions of each design variable.